PERAN PENYULUH KEHUTANAN TERHADAP PERUBAHAN SOSIAL MASYARAKAT DALAM PEMANFAATAN HASIL HUTAN BUKAN KAYU - Pandoyo, Feri Markop Runtu; Zainal, Sofyan; wati, Pur (JURNAL HUTAN LESTARI, 2013)
Descriptive analysis show the characteristics of societies is different, based on the level income average the respondents included in the high income category 20,15%, medium 61,56%, and low category 17,95%. While, based on the level knowledge there are three categories : high 71,79%, medium 21,80%, and for the low category 6,41% and for the characteristics of the respondents, based on counseling program with 78 respondents, high category 89,74% with 70 respondents, medium 5,13% with 4 respondents, and the low category 5,13% with 4 respondents. And the next category is characteristics respondents. Role of forestry extension the social changes the utilization non timber forest products, having a percentage for the category 91,02% with 71 respondents, for the medium category 5,31% with 4 respondents while for the low category 3,85% with 3 respondents. Inferential analysis results indicate that there is a significant relation between counseling program (33,61) with the role of forestry extension towards social changes and there is no significant relation between the level of income (1,27), knowledge (6,94) with counseling role social forestry in Tunggul Boyok Village. Keyword: Role, forestry extension, social society change, and forest product non-timber